2021
DOI: 10.5614/j.eng.technol.sci.2021.53.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Dioscorea hispida Starch as a Novel Natural Coagulant in Textile Wastewater Treatment

Abstract: The process of coagulation-flocculation using Dioscorea hispida starch as a natural coagulant was investigated for the purification of textile effluent from several dyeing and finishing mills. The major parameters tested were COD, turbidity, and color. Prior to conducting the experiments, the general physical characteristics of Dioscorea hispida starch were investigated. The optimal conditions, pH and coagulant dosage were assessed using a jar test. The results demonstrated that the Dioscorea hispida starch yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Diascora hispida is a plant found in the tropic and subtropic regions of the world, especially in West Africa, the Caribbean, and Southeast Asia [110]. Diascora hispida was used as a natural coagulant to treat textile wastewater effluent and could achieve an efficiency of 28%, 94% and 64% at an optimum pH [111]. Banana has the highest production amount in Southeast Asia [112], and a study conducted on banana peels as a natural coagulant showed the removal of 88% of turbidity under optimum conditions [16].…”
Section: Use Of Natural Coagulants In Southeast Asiamentioning
confidence: 99%
“…Diascora hispida is a plant found in the tropic and subtropic regions of the world, especially in West Africa, the Caribbean, and Southeast Asia [110]. Diascora hispida was used as a natural coagulant to treat textile wastewater effluent and could achieve an efficiency of 28%, 94% and 64% at an optimum pH [111]. Banana has the highest production amount in Southeast Asia [112], and a study conducted on banana peels as a natural coagulant showed the removal of 88% of turbidity under optimum conditions [16].…”
Section: Use Of Natural Coagulants In Southeast Asiamentioning
confidence: 99%
“…However, recent findings demonstrated that applying unmodified starch as a single flocculant requires a greater dosage to achieve high removal performance [12]. Yusof et al [13] employed unmodified Dioscorea hispida starch through a coagulation process and discovered that the maximum COD reduction was only 22% using a large dosage of 2500 mg/L in wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%